2018
DOI: 10.1007/s12094-018-1941-1
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial membrane protein 2: a novel biomarker for circulating tumor cell recovery in breast cancer

Abstract: EMP2 is superior to EpCAM for capturing both MCF7 and MDA-MB-231 cells. Additionally, EMP2 is a novel biomarker and capable of capturing breast cancer cells in patient blood samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Also, the anti-EMP2 monoclonal antibody captured over 80% of the total MDA-MB231 cells. EMP2 might be a more efficient biomarker for capturing CTC in breast cancer blood samples and is worthy of further assessments in clinical trials [ 100 ].…”
Section: Biological Functions Of the Pmp22 Protein Familymentioning
confidence: 99%
“…Also, the anti-EMP2 monoclonal antibody captured over 80% of the total MDA-MB231 cells. EMP2 might be a more efficient biomarker for capturing CTC in breast cancer blood samples and is worthy of further assessments in clinical trials [ 100 ].…”
Section: Biological Functions Of the Pmp22 Protein Familymentioning
confidence: 99%
“…In addition, the functions and potential mechanism of EMP2 are varied in different type of cancers. Recently, Chen et al reported that EMP2 is highly expressed in circulating breast cancer cells 38. And the elevated EMP2 expression is associated with poor prognosis of glioma patients 39.…”
Section: Discussionmentioning
confidence: 99%
“…The level of EMP2 protein is positively associated with cancer progression, which is supported by findings that EMP2 is expressed in 67% of lymph node metastases and is linked with lymphovascular invasion [90]. Recently, EMP2 protein seems to have been identified as a novel biomarker to effectively capture circulating tumor cells (CTCs) in blood samples from patients with breast cancer [93]. In addition, CTCs are more effectively detected in the samples from the pulmonary vein than the peripheral vein, even in the early stage of the cancer [94].…”
Section: Involvement Of Emps In Cancer Metastasismentioning
confidence: 97%